Schedule quality evaluation for Construction Project Management - Bragadin, Marco Alvise; Kahkonen, Kalle (TECHNE - Journal of Technology for Architecture and Environment, 2020)
The construction schedule is the most important construction document as it indicates total project duration, project stages and times of activities, costs, logical sequences, quality and safety. Hence, the quality of a phase schedule presented by a contractor must be assessed by the owner’s consultant either before the commencement of works or during the bidding phase. Only few international standards concerning schedule quality exist, and most of them are not specific for construction. A construction-oriented schedule quality evaluation procedure, based upon a set of 75 requirements has been proposed. Three different versions of a construction schedule for a case study of a seismic rehabilitation project have been evaluated with the aim of performing the proposed method’s proof-of-concept.